(untitled) (Journal of the College of Education for Women, 2019)
In this research, beam expander, BEX, is explained and designed for illuminating theremote flying target. The BEX is optically designed to be suited for Nd:YAG laser of givenspecifications. The BEX is modified to be zoom one to meet the conditions of preventing thereceiving unit; i.e the photodetector, from getting saturated at near and far laser tracking.Decollimation could be achieved by automatic motor, which controls zoom lens of the BEXaccording to the required expansion ratio of beam expander